Analisis Efektivitas UU No 6 Tahun 2014 Dalam Penggunaan APBDes Untuk Kesejahteraan Masyarakat Desa (Studi Desa Linggar Galing, Pondok Kubang, Bengkulu Tengah) - Tigor Sitorus; Evsa Wulan Suri; Mulyadi Gembar (AMMA : Jurnal Pengabdian Masyarakat, 2024)
The purpose of this study is to find out the use of APBDes in village development in road infrastructure and assistance from the village head in prospering the community. The method used in this study is a qualitative method for descriptive data analysis, the research is carried out by observation, interview, questionnaire, and documentation.